Interview Observation Report of SMKN 1 Glagah Banyuwangi - Annisa Dwi Rahayu; Yunia Widianti (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2026)
History learning plays a strategic role in shaping historical awareness, nationalism, and critical thinking skills in students. However, in practice, various obstacles are still encountered, such as low student interest in learning and limited creativity of educators in utilizing learning media. This research is motivated by the need to directly understand the process of planning and implementing history learning, particularly regarding the integration of learning media and the Learning Objectives Flow (ATP) in the context of the applicable curriculum at SMKN 1 Glagah Banyuwangi. (1) The objectives of this research are to identify the implemented curriculum, analyze the history learning process, examine the use of learning methods and media, and identify the challenges faced by teachers and students in learning history. (2) The research method used is a qualitative approach with observation and interview techniques. The research subjects included the Vice Principal for Curriculum, history subject teachers, and class X DPIB 2 students. Data were collected through structured interviews, classroom observations, and documentation, then analyzed descriptively. (3) The results of the research indicate that the school has implemented a more flexible and student-centered Independent Curriculum. didik. Guru sejarah menerapkan metode blended learning dengan memanfaatkan media video dan mengaitkan materi sejarah dengan kompetensi kejuruan siswa. Meskipun demikian, Obstacles still exist in the form of low focus and interest in learning among some students, as well as limited variety of learning media. From the students' perspective, the use of audiovisual media is considered more engaging and facilitates understanding of the material. The conclusion of this study indicates that the integration of learning media with planning through ATP contributes positively to the effectiveness of history learning. Despite facing several challenges, teachers' adaptive efforts and students' use of technology are supporting factors in creating more contextual, relevant, and meaningful history learning.